The properties of HPMC: PEO extended release hydrophilic matrices and their response to ionic environments - Hu, Anran; Chen, Chen; Mantle, Michael D.; Wolf, Bettina; Gladden, Lynn F.; Rajabi-Siahboomi, Ali; Missaghi, Shahrzad; Mason, Laura; Melia, Colin D. (Springer, 2017)
Purpose